A normative approach to reducing illegal music downloading: The persuasive effects of normative message framing. Issue 1 (February 2015) - Moon, Shin-Il; Kim, Kitae; Feeley, Thomas Hugh; Shin, Dong-Hee
Highlights Persuasive effects of message framing on reactions to campaign messages. A survey was conducted on illegal music downloading. Positively worded messages were more influential than negatively worded ones. The findings have theoretical and practical implications.